ASSESSMENT OF THE RISK TO THE HEALTH OF THE POPULATION OF AN INDUSTRIAL CENTER DUE TO THE EXPOSURE OF ATMOSPHERIC EMISSIONS OF THE PETROLEUM DEPOT - Кислицына, Вера Викторовна; Суржиков, Дмитрий Вячеславович; Ликонцева, Юлия Сергеевна; Штайгер, Варвара Адамовна (Medicine in Kuzbass, 2023)
The aim of the research was the assessment of the risk to the health of the population of an industrial center due to the air pollution by the emissions from a petroleum depot. Materials and methods. The volume of maximum permissible emissions was used in the work. The assessment of the distribution and impact of atmospheric emissions was carried out at 35 calculated points selected on the basis of a map of the city of Novokuznetsk, the Kemerovo region. The maximum and average annual concentrations of pollutants were calculated using the UPRZA «EKOtsentr-Standart» software package. The values of the risk of chronic intoxication and carcinogenic risk were calculated on the basis of the Guidelines P 2.1.10.1920-04, the methods of A.P. Shcherbo et al., G.G. Onishchenko et al. The risk values were determined taking into account the impact of background concentrations of pollutants. A comparison of the obtained risk values with the acceptable levels was carried out. Results. Priority pollutants entering the city air from the sources of the petroleum depot were identified: benzene, sulfur dioxide, nitrogen dioxide, toluene, carbon (soot), nitrogen oxide, xylene, carbon monoxide. At all points of exposure, no excess of the maximum and average annual concentrations of the substances entering the atmosphere during the operation of the petroleum depot was observed. The total risk values of chronic intoxication and carcinogenic risk did not exceed the acceptable level. The total risk values of chronic intoxication calculated taking into account the effect of background concentrations of pollutants exceeded the acceptable level at all points of exposure by 2.6-3.9 times. The micro-districts of the city that were most susceptible to the influence of atmospheric emissions from this industrial facility had been identified. Conclusion. The unfavorable environmental situation in the city with the intensive industrial development leads to an increase in the risk of chronic intoxication for the health of the population. The activities of the petroleum depot do not have a significant impact on the environment and the health of the city’s population.